2021
DOI: 10.3390/agriculture11080782
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas putida Isolation and Quantification by Real-Time PCR in Agricultural Soil Biodegradable Mulching

Abstract: To reduce the plastic waste problem in agriculture, biodegradable plastic (BP) mulch films have become of key importance thanks to their biodegradability and beneficial effects on crops. However, at present, BPs cannot always replace conventional plastics, because biodegradation is governed by many biotic and abiotic factors under field conditions. This research aimed at isolating and identifying, from soil particles directly attached to the surface of BP samples, the microorganisms responsible of degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…At present, some studies have made corresponding progress. For instance, Fontanazza et al [ 60 ] isolated and identified the mesophilic bacterium Pseudomonas putida from soil particles and found that the bacterium Pseudomonas putida was responsible for the degradation of biodegradable plastic. This may lead to the use of plastic-degrading microorganisms for amendments to the soil where plastics need to be degraded or to accelerate the degradation process.…”
Section: Discussionmentioning
confidence: 99%
“…At present, some studies have made corresponding progress. For instance, Fontanazza et al [ 60 ] isolated and identified the mesophilic bacterium Pseudomonas putida from soil particles and found that the bacterium Pseudomonas putida was responsible for the degradation of biodegradable plastic. This may lead to the use of plastic-degrading microorganisms for amendments to the soil where plastics need to be degraded or to accelerate the degradation process.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa isolated from sewage water-contaminated surface soil incubated in nutrient broth (NB) medium for one month PP showed a weight loss of 5.37% [ 48 ]. Moreover, other species of the Pseudomonas , such as Pseudomonas citronellolis [ 49 ], Pseudomonas putida [ 50 ], Pseudomonas alcaligenes [ 51 ], and Pseudomonas fluorescens [ 52 ], have also been shown to degrade different types of plastics.…”
Section: Microbial Degradation Of Plasticsmentioning
confidence: 99%